Type II Transmembrane Serine Protease (TTSP) deregulation in cancer - Webb, Siobhan, L (Frontiers in bioscience, 2011)
The Type II transmembrane serine proteases (TTSP) are a relatively newly identified family of proteolytic enzymes that have become the subject of intense scrutiny in the field of cancer research. Advances in genome screening technology have enabled the identification of putative members and the further characterization of existing members. The TTSPs are involved in a diverse range of physiological functions and new roles continue to be discovered. A large majority of these proteases appear to play crucial roles in the development of disease, especially cancer development and progression. This review presents the current knowledge of the biological role of those TTSPs that have been identified in the development and progression of human cancers.